2010
DOI: 10.1007/s10641-010-9717-7
|View full text |Cite
|
Sign up to set email alerts
|

Egg thiamine concentration affects embryo survival in Lake Erie walleye

Abstract: We quantified thiamine in eggs of Lake Erie walleye to determine if differences exist between spawning stocks within the Maumee and Sandusky rivers, both of which drain into the Western Basin. In spring 2004, eggs of walleye were collected in the Maumee River at three occasions (early, peak and late of the spawning run) and in the Sandusky River during the spawning run. After collection, eggs were fertilized with a known amount of milt, incubated and embryo survival was determined at the pigmented eyed stage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…Zooplankton "spikes" that are observed in Lake Oahe during June yield densities that are comparable to those in eutrophic systems (Fincel 2011) and may free larval Walleye from interspecific competition. The levels of thiamine concentration in Walleye eggs from Lake Oahe (Barnes et al 2005) were similar to those that were measured in other Walleye populations with primary prey species containing thiaminase (Honeyfield et al 2007;Rinchard et al 2011), but natural reproduction was evident across all years with occasional large year-classes, indicating that the thiamine concentration in eggs is not having a strong negative effect on reproduction. Stock abundance was not significantly correlated to recruitment, indicating that Walleye recruitment in Lake Oahe was regulated by density-independent factors during the years that were included in this study.…”
Section: Locationsupporting
confidence: 76%
See 1 more Smart Citation
“…Zooplankton "spikes" that are observed in Lake Oahe during June yield densities that are comparable to those in eutrophic systems (Fincel 2011) and may free larval Walleye from interspecific competition. The levels of thiamine concentration in Walleye eggs from Lake Oahe (Barnes et al 2005) were similar to those that were measured in other Walleye populations with primary prey species containing thiaminase (Honeyfield et al 2007;Rinchard et al 2011), but natural reproduction was evident across all years with occasional large year-classes, indicating that the thiamine concentration in eggs is not having a strong negative effect on reproduction. Stock abundance was not significantly correlated to recruitment, indicating that Walleye recruitment in Lake Oahe was regulated by density-independent factors during the years that were included in this study.…”
Section: Locationsupporting
confidence: 76%
“…Elevation Change is the difference in end of May elevation in a given year from the previous year, Tribs is the sum of cumulative inflow from the Grand and Moreau rivers (two large tributaries to Lake Oahe), Condition is the mean relative weight of age-4 and older Walleye during the previous August, Temp is the average May air temperature in Mobridge, South Dakota, and Fingerling is the number of stocked fingerlings (*P < 0.05). 1997;Mercado-Silva et al 2007) or through early mortality syndrome caused by thiamine deficiency (Honeyfield et al 2007;Mercado-Silva et al 2007;Rinchard et al 2011). The size and complexity of Lake Oahe likely decreases the spatial overlap between larval Walleye and Rainbow Smelt, limiting their interaction.…”
Section: Locationmentioning
confidence: 99%
“…; Rinchard et al . ), but parental and/or egg thiamine depletion only occurs with specific broodstock diets, that is, raw seafood products containing thiaminase (Kreutzmann & Lehmitz ).…”
Section: Broodstock Nutrition: Nutritional Influences On the Process mentioning
confidence: 99%
“…Thiamine thresholds for direct mortality vary among fish species, with estimates of egg thiamine thresholds for lake trout, Chinook salmon Oncorhynchus tshawytscha, coho salmon Oncorhynchus kisutch and Atlantic salmon Salmo salar ranging from 0.41 to 2.99 nmol·g −1 (Fisher et al, 1996;Honeyfield et al, 2005;Wolgamood et al, 2005;Werner et al, 2006;Fitzsimons et al, 2007). Rainbow smelt Osmerus mordax larvae hatched from eggs with a mean thiamine content of 2.7 nmol·g −1 showed signs of TDC (Chalupnicki et al, 2010), and walleye embryos from the Maumee River (Lake Erie) showed reduced survival below egg thiamine concentrations of approximately 6 nmol·g −1 (Rinchard et al, 2011). A conservative interpretation of these results indicates that egg thiamine concentrations below 1 nmol·g −1 are commonly associated with TDC, although effects may also be observed at higher concentrations.…”
Section: Discussionmentioning
confidence: 94%
“…It is hypothesized that TDC in lake trout is caused by a diet composed of a high proportion of alewife Alosa pseudoharengus , which are high in thiaminase, a thiamine-degrading enzyme. Thiamine deficiency has also been reported in other fish species (Breitholtz et al, 2001;Werner et al, 2006;Fitzsimons et al, 2007;Chalupnicki et al, 2010;Rinchard et al, 2011) but the full extent of its occurrence and significance to fish populations is unknown. Invasive dreissenid mussels Dreissena bugensis and Dreissena polymorpha have been increasing in abundance in the Great Lakes (Nalepa et al, 2007(Nalepa et al, , 2009a and have extremely high thiaminase activity levels .…”
Section: Introductionmentioning
confidence: 99%